Acumulação e balanço de sedimentos em superfícies asfálticas em área urbana de Santa Maria - RS - Dotto, Cintia Brum Siqueira (2006)
This paper presents the results from a street gutter sediment characterization study in two asphalted streets in Santa Maria - RS. It also presents the results from the samples collected at the station installed at the outlet of a drainage system. One of the dry sampled streets is the contribution area of the system. The field and laboratory tests were accomplished from April to December 2005. Dry sediment sampling was done in three different periods, each one of them with about 30 days. The solid-liquid samples were accomplished during some significative storm events in order to determine the suspended sediment concentration and load from the drainage system. The dry sediment samples results indicate that the sediment buildup process on impervious surfaces occurs relatively quickly after a raining event. The accumulated particles washoff depends on the rainfall and runoff characteristics and the data indicate the rainfall events remove only a small portion of the sediments found on the surfaces. The particle size analysis indicate that the two sampled streets present sediments with a measured median diameter of 0,35 mm The solidliquid samples concentration values ranged from 8,0 to 6.000 mg/L. These samples particle size analysis presented that the superficial flow carries particles, which range from the finer to more coarser, with a median diameter ranging from 0,01 mm to 12 mm, verifying the street sediment washoff through the drainage system.